Perancangan Kriptografi Block Cipher Menggunakan Pola Logo Media Sosial - Bulamey, Thea Thiranadya Mardita; Hendry, Hendry (STMIK Budi Darma, 2021)
In this research, 64-bit Block Cipher Cryptography was designed based on the Social Media Logo Pattern, this design aims to produce a new cryptographic system, and aims to secure data or information in the form of text. In designing cryptography using Social Media Patterns, correlation tests have been carried out 24 times so as to produce the best pattern sequence with an average correlation value of 0.014425413 with a 1-2-4-3 sequence pattern. After finding the best pattern, 10 rounds are carried out where in each cycle there are 4 processes consisting of 4 patterns for the plaintext process and 4 patterns for the key process, and accompanied by S-Box substitution in each process so that the avalanche effect has a significant increase. In this research, the avalanche effect test was also carried out. In each avalanche effect test, it shows that the S-Box has an effect on the encryption process because in each cycle it has an avalanche effect that reaches 50%. So it can be said that the ciphertext generated by block cipher cryptography based on the social media logo pattern has random output results so that it can be used to secure data or information in the form of text